-BASED ANALYSIS OF GRAMMATICAL TRANSFORMATIONS IN FRENCH-RUSSIAN LITERARY TRANSLATION - Khamidova Nargiza Yusufovna (International Journal of Literature and Language Studies, 2026)
The present study explores grammatical transformations in French-Russian literary translation through a corpus-based approach. Due to significant structural differences between French and Russian, translators frequently apply various grammatical transformations to preserve meaning, style, and communicative effect in translated literary texts. The research analyzes parallel corpora consisting of original French literary works and their Russian translations to identify the most common transformation techniques. The findings demonstrate that transposition, sentence restructuring, grammatical substitution, omission, and addition are widely employed to achieve equivalence between the source and target texts. The study highlights the importance of corpus linguistics as a reliable methodological tool for investigating translation patterns and understanding the relationship between linguistic structure and translation practice. The results contribute to the development of translation studies and provide insights into the grammatical adaptation of literary texts across languages [1–5].